(untitled) (Research, Society and Development, 2020)
Gluten-free and lactose-free cakes are present in the food market, but they may contain ingredients with amino acid phenylalanine, restricting their consumption by patients with phenylketonuria. The objective of this work was to use flaxseed gel (GL) and yam mucilage (MI) to replace albumin, eggs and soy extract of muffins without the addition of sucrose, gluten and lactose. A complete central rotational design 22 (p <0.1) was conducted with two independent variables, GL and MI contents, ranging from 10 to 20 g and 20 to 40 mL respectively. The technological characteristics of the batter and produced muffins were evaluated. The addition of GL and MI did not influence the density of the dough and the water activity, firmness, color L*, a*, b* of the crust and color a* of the muffin core. The GL positively influenced the specific volume (R2: 0.54), L* the luminosity (R2: 0.71) and the color b* (R2: 0.60). It was possible to replace eggs, albumin and soy extract of muffins with MI and GL, which may represent a new option for consumers of products with low-protein/ no-protein ingredients.